1990
DOI: 10.1111/j.1744-6570.1990.tb00681.x
|View full text |Cite
|
Sign up to set email alerts
|

THE RELATIONSHIP OF INTERVIEWERs' PREINTERVIEW IMPRESSIONS TO SELECTION AND RECRUITMENT OUTCOMES

Abstract: Many interviewers must handle the competing demands of assessment and recruitment when conducting interviews. Both interviewers and applicants in a college placement setting provided their perceptions of each other and the interview process. The present study explored possible mediators and moderators of the relationship of interviewers' preinterview impressions of applicants to their postinterview impressions of the same applicants, as well as the effects on recruiting success. Consistent with a process model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 39 publications
3
74
0
Order By: Relevance
“…Although initial impressions can change when more jobrelated information becomes available, they often impact final decisions in interviews (Stewart et al 2008). For instance, interviewers are likely to engage in confirmatory processes by asking questions and evaluating responses in ways that confirm their initial impressions (Derous et al in press;Dougherty et al 1994;Macan and Dipboye 1990). As such, applicant smoking status triggers biases similar to those triggered by the other stigmatizing features such as age, ethnicity, or obesity.…”
Section: Findings and Theoretical Implicationsmentioning
confidence: 94%
“…Although initial impressions can change when more jobrelated information becomes available, they often impact final decisions in interviews (Stewart et al 2008). For instance, interviewers are likely to engage in confirmatory processes by asking questions and evaluating responses in ways that confirm their initial impressions (Derous et al in press;Dougherty et al 1994;Macan and Dipboye 1990). As such, applicant smoking status triggers biases similar to those triggered by the other stigmatizing features such as age, ethnicity, or obesity.…”
Section: Findings and Theoretical Implicationsmentioning
confidence: 94%
“…Screening and selection of the candidates for the initial job interviews are usually derived from objectively assessed information or 'paper credentials' (Macan and Dipboye, 1990) such as the level of academic performance and the level of participation in extracurricular activities. It is assumed at this stage of the recruitment process that the recruiters do not know and have not seen the candidates.…”
Section: Model Development and Hypothesis Formulationmentioning
confidence: 99%
“…Because it is likely that in most hiring situations the person conducting the hiring will review information about the candidate prior to the face-to-face interview, as they will do in our study, it is necessary to see what effect this prior information may have on judgments. In previous research, it has been found that interviewers typically form pre-interview impressions or judgments about the candidate that may be hard to change from this prior information (e.g., a resume or application), (Macan and Dipboye 1990). In fact, there is the possibility that interviewers may feel compelled to remain consistent with these prior judgments of the candidate, particularly if those judgments were made public, even if some additional information about the candidate (i.e., pregnancy) gathered in the interview might change their perceptions.…”
Section: Check For Consistency Effectmentioning
confidence: 99%